2015
DOI: 10.1038/ismej.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent adaptive resistance allows swimming bacteria to colonize an antibiotic gradient

Abstract: During antibiotic treatment, antibiotic concentration gradients develop. Little is know regarding the effects of antibiotic gradients on populations of nonresistant bacteria. Using a microfluidic device, we show that high-density motile Escherichia coli populations composed of nonresistant bacteria can, unexpectedly, colonize environments where a lethal concentration of the antibiotic kanamycin is present. Colonizing bacteria establish an adaptively resistant population, which remains viable for over 24 h whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 45 publications
1
48
1
Order By: Relevance
“…At ΔΨ o = −1.5 MPa, we observed bacterial dispersal exerting negative effects on benzoate biodegradation (Figure 3E ). Recently, it was found that the colonization of stress-affected environments requires a critical population density in order to maintain activity in an antibiotic landscape (Hol et al, 2016 ). Possibly, this was the case also in our system for low ΔΨ o and the primary colonizers leaving the inoculation site were not able to establish, thus reducing the overall activity in the system.…”
Section: Discussionmentioning
confidence: 99%
“…At ΔΨ o = −1.5 MPa, we observed bacterial dispersal exerting negative effects on benzoate biodegradation (Figure 3E ). Recently, it was found that the colonization of stress-affected environments requires a critical population density in order to maintain activity in an antibiotic landscape (Hol et al, 2016 ). Possibly, this was the case also in our system for low ΔΨ o and the primary colonizers leaving the inoculation site were not able to establish, thus reducing the overall activity in the system.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 The TAAD concentrations above MPC at a surgical incision site, the site of potential bacterial contamination, may improve SSI prophylaxis and bacterial resistance prevention. 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…However, beyond the direct interaction between APs and bacterial targets, APs can be tolerated by certain bacterial species through collective mechanisms. The collective tolerance mechanisms are relatively well studied for classical antibiotics [19,20] when compared with antimicrobial peptides, and their implications for antibiotic treatment are well demonstrated in the literature [21][22][23][24]. For antimicrobial peptides, bacteria may exhibit collective tolerance through mechanisms such as membrane-displayed proteases that degrade APs [25 -27] and secreted molecules including lipids, vesicles and proteins that sequestrate APs [16][17][18]28].…”
Section: Introductionmentioning
confidence: 99%